Discourse in a Material World. (28th December 2014) - Hardy, Cynthia; Thomas, Robyn
Abstract We challenge recent assertions that discourse studies cannot de facto address materiality. We demonstrate how a Foucauldian theorization of discourse provides a way to analyse the co‐constitutive nature of discursive and material processes, as well as explore the power relations implicated in these relationships. To illustrate our argument, we identify exemplary studies that have effectively combined a study of discourse and different aspects of materiality – bodies, objects, spaces, and practices. In doing so, we show how discourse scholars are able to study both materiality and power relations.